2021
DOI: 10.1155/2021/7929756
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of Energy/Exergy for Absorber Pipes of Linear Parabolic Concentrating Systems

Abstract: In this paper, the physical parameters of the absorber pipe of a linear parabolic collector have been investigated. The types of solar collectors, specifically the linear parabolic collector, have been comprehensively studied. Then, the mathematical model of heat transfer in the absorber pipe of the collector has been presented based on valid references. Numerical solutions of the equations related to the absorber pipe were performed by MATLAB software, and the effects of the physical parameters of the absorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The correct selection of the absorber configuration and the heat exchanger is crucial for making competitive absorption solar cooling systems against those based on vapor compression (Alayi et al, 2021b; Dhindsa, 2021). In this context, several studies have shown that the plate heat exchangers (PHEs) used as the absorber element in bubble absorption mode improve the heat transfer, the contact of the refrigerant with the solution, and allow modular designs (Castro et al, 2009; Chan et al, 2018; Lee et al, 2002; Lima et al, 2021; Tae Kang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correct selection of the absorber configuration and the heat exchanger is crucial for making competitive absorption solar cooling systems against those based on vapor compression (Alayi et al, 2021b; Dhindsa, 2021). In this context, several studies have shown that the plate heat exchangers (PHEs) used as the absorber element in bubble absorption mode improve the heat transfer, the contact of the refrigerant with the solution, and allow modular designs (Castro et al, 2009; Chan et al, 2018; Lee et al, 2002; Lima et al, 2021; Tae Kang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of thermal systems based on renewable energies, this computational tool has been successfully implemented for the modeling and optimization of conventional geothermal processes and with the organic Rankine cycle, with relatively high precision (Haghighi et al, 2021). They have also been used to improve the thermal performance of various components such as heat exchangers(Alayi et al, 2021a), absorber tubes (Alayi et al, 2021b), and energy storage systems (Alhuyi Nazari et al, 2021a) in solar thermal installations for process heat and desalination (Alhuyi Nazari et al, 2021b). On the other hand, ANN has also proven to be a helpful alternative for modeling the physical properties of thermo-fluids to improve the energy conversion processes in various thermal systems; being relevant for those cases where they are used for thermal solar systems (Rashidi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%